(untitled) (Economics and region, 2024)
The convenience of distance selling is already forcing companies to develop new advertising strategies. What will attract more people’s attention and interest? As is well known, advertising in international trade began with the development of trade between countries. International trade is recognised as the sum of commercial activities carried out by the countries of the world based on transactions in goods and services and import-export relations. In particular, international trade can be considered as the most positive result of globalisation. Many factors stimulate the development of international trade. One of these factors is advertising. This activity and its results have developed from ancient times to the present day. Even today, it maintains its relevance by creating new demands. Advertising should not be seen as a mere method of disseminating information. It is carried out for a specific purpose - to create demand for the product or to improve the image of the company. From this point of view, advertising in global trade serves as the driving force that keeps the wheels of corporate progress turning. The main relevance of the topic is that international advertising is much more complicated than local advertising and requires special research. It is also worth adding that products produced in the local market are usually known as the country’s brand when they enter the foreign market. If it succeeds, it can be considered a success for the country in the region. From this point of view, it is important to choose the right foreign market and develop an international advertising strategy suitable for that market. The first thing that all companies wishing to enter a foreign market should do is research the market and develop a proper advertising strategy. A well thought out advertising strategy is half the success. Advertising is important for both B2C and B2B sales. However, in international sales, advertising is more often used for B2B sales. Therefore, advertising comes in different forms. This article presents some of these forms.